VD_FINDINFO MP / 2015 / 7 vom 17. Juli 2015 - VD Tribunal cantonal (2015)
CONCURRENCE DÉLOYALE, DÉNIGREMENT, MESURE PROVISIONNELLE | 2 CL, 31 CL, 13 LCD, 2 LCD, 3 al. 1 let. a LCD, 3 LCD, 129 al. 1 LDIP, 136 LDIP, 261 al. 1 CPC (CH), 261 CPC (CH), 262 CPC (CH), 5 al. 1 let. d CPC (CH), 5 CPC (CH)